A study on vague-valued hesitant fuzzy graph with application - Rao, Yongsheng; Chen, Ruxian; Kosari, Saeed; Talebi, A. A.; Mojahedfar, Masome (Frontiers in Physics, 2022)
The hesitant fuzzy graph (HFG) is one of the most powerful tools to find the strongest infuential person in a network. Many problems of practical interest can be modeled and solved by using HFG algorithms. HFGs, belonging to the FGs family, have good capabilities when faced with problems that cannot be expressed by FGs. Vague-valued hesitant fuzzy graph (VVHFG) is the generalization of HFG. A VVHFG is a powerful and useful tool to find the influential person in various parts, as meetings, conferences and every group discussion. In this paper, we introduce a new concept of VVHFG. Our purpose is to develop a notion of VVHFG and also to present some basic definitions, notations, remarks and proofs related to VVHFGs. We propose a numerical method to find the most dominating person using our proposed work. Finally, an application of VVHFG in decision making has been introduced.